Can the Experience of Participatory Development Help Think Critically about 'Patient and Public Involvement' in UK Healthcare?. (September 2019) - Mosse, David
The expansion of spaces for 'patient and public involvement' in health systems in the UK is a relatively recent phenomenon, and yet 'participation' as a principle for planned interventions in international development is well established as a field of practice and controversy. Development workers and scholars have passed through moments of enchantment and disenchantment with the idea that the true source of innovation, expertise, and workable (and sustainable) solutions is to be found not in the professionals but in communities of experience. Making 'local knowledge' the basis of interventions has proved unexpectedly problematic. How could incommensurable forms of knowing, across steep gradients of power be bridged? This article describes a decade-long experiment in participatory development in a remote Adivasi (tribal) region of western India in order to suggest the relevance of this experience for the very different context of patient and public involvement in healthcare settings. In particular, it highlights some general points about knowledge practices at the interface, and the human tendency to adjust, mirror, mimic, loop, and in other ways make the 'patient–professional' interface itself hard to navigate. The article suggests that self-reflective insight into these social processes is necessary for effective 'engagement' by professional and lay actors alike.